Recent Advances in Graphene Quantum Dots: Synthesis, Properties, and Applications. Issue 10 (4th July 2018) - Haque, Enamul; Kim, Jeonghun; Malgras, Victor; Reddy, Kakarla Raghava; Ward, Alister C.; You, Jungmok; Bando, Yoshio; Hossain, Md. Shahriar A.; Yamauchi, Yusuke
Abstract: Here, an interesting, new 0D material is presented: graphene quantum dots. The new properties arising from quantum confinement and edge effects after converting 2D graphene into graphene quantum dots have attracted great interest in various disciplines, such as physics, biology, materials, and chemistry. Here, the recent technological advances in the field of graphene quantum dots reported in the literature on both a theoretical and an experimental basis are highlighted. Various synthesis methodologies and physical properties are discussed, along with their implementation in energy (supercapacitors, fuel cells, photovoltaic devices, light‐emitting diodes), biomedical (biosensors, drug delivery, bioimaging), and environmental applications. Abstract : Methods for the synthesis of graphene quantum dots (GQDs) are summarized, and their representative chemical and physical properties are briefly introduced. Various interesting applications of GQDs in electronics, energy, biomedical, and environment, for example, are introduced, and future research directions are discussed.